The Genome Clinic: A Multidisciplinary Approach to Assessing the Opportunities and Challenges of Integrating Genomic Analysis into Clinical Care. Issue 5 (7th April 2014) - Bowdin, Sarah; Ray, Peter N.; Cohn, Ronald D.; Meyn, M. Stephen
<x xml:space="preserve">Abstract</x> Genetic medicine uses knowledge of an individual's genomic variants to guide health care decisions throughout life, to anticipate, diagnose, and manage disease. We review the opportunities and challenges presented by this new clinical paradigm and describe a research project, the "SickKids Genome Clinic, " that addresses these issues by enabling a wide range of studies ranging from the development of clinical bioinformatics tools and the discovery of disease genes to health policy inquiries and assessment of clinical care. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>